2020
DOI: 10.4018/ijicte.2020040103
|View full text |Cite
|
Sign up to set email alerts
|

Mobile and Adaptive Learning Application for English Language Learning

Abstract: Mobile learning is considered a new phase of e-learning which gives the opportunity to learn more effectively and efficiently. In addition, the use of mobile devices for leaning is more sophisticated and more useful. The m-learning has become available anywhere and anytime for all students and professors. Moreover, the features of these mobile devices include ease of use in every place and time, very reasonable cost for students, and the ability to communicate through the internet or mobile networks, encouragi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 3 publications
1
15
0
1
Order By: Relevance
“…In contrast, an architectural model was proposed in the study. The Pedagogical model, and learner model, were used by pilot testing ( Bourekkache & Kazar, 2020 ), whereas a mobile game for tenses’ SOS Table’ was developed. The evaluation measured its effectiveness, user's motivation, acceptance, and attitude within the Framework of mobile learning tools ( Önal, Çevik & Şenol, 2019 ).…”
Section: Assessment and Discussion Of Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, an architectural model was proposed in the study. The Pedagogical model, and learner model, were used by pilot testing ( Bourekkache & Kazar, 2020 ), whereas a mobile game for tenses’ SOS Table’ was developed. The evaluation measured its effectiveness, user's motivation, acceptance, and attitude within the Framework of mobile learning tools ( Önal, Çevik & Şenol, 2019 ).…”
Section: Assessment and Discussion Of Research Questionsmentioning
confidence: 99%
“…The methodology is the basic techniques or methods used to identify, collect, retrieve, and interpret information on the topic ( Paul, 2000 ). A quantitative study using a quasi-experiment (Pre-test and Post-test) was conducted by ( Hsu, Hwang & Chang, 2013 ) ( Wu, 2018 ) ( Chang et al, 2013 ) ( Kalogirou, Beauchamp & Whyte, 2017 ) ( Fisser, Voogt & Bom, 2012 ) to collect data through questionnaires whereas, a quantitative study using questionnaire only was conducted by ( Zhang, 2016 ) ( Kohnke, Zhang & Zou, 2019 ) ( Bourekkache & Kazar, 2020 ). A mixed-method approach was used ( Amer, 2014 ) ( Botero, Questier & Zhu, 2018 ) ( Ou-Yang & Wu, 2016 ; Quan, 2016 ) ( Önal, Çevik & Şenol, 2019 ; Zhang & Pérez-Paredes, 2019 ) ( Ishaq et al, 2020b ) to conduct interviews and questionnaire for the collection of information, whereas a qualitative approach in which interviews were conducted by ( Hazaea & Alzubi, 2018 ) ( Makoe & Shandu, 2018 ).…”
Section: Assessment and Discussion Of Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The educational benefits of using mobile technologies for English language learning are often explored under mobile-assisted language learning (MALL) [14]- [17] and mobile-learning (m-learning) (e.g., [18]- [21]). For mobile learning applications, one of its main benefits is its mobility and portability [16], [18]- [20]. As shown, most students who owned mobile devices used their mobile application for language learning at the comfort of their home [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additional recommendations are based on the study of Bourekkache, Kazar [18], Kacetl, and Klímová [20] in which they suggested that future undertakings of mobile applications for English language learning should focus on one of the four basic language skills (i.e., listening, speaking, reading, and writing). Future researchers may explore the possibility of adding new least mastered topics as well as making the application and the animated character Alvin intelligent through the help of different artificial intelligence techniques (e.g., data analytics and machine learning).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%